Valuing convenience in public transport in the Korean context - Sungwon Lee (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2013)
Public transport patronage has been continuously declining in major Korean cities as levels of car ownership rise. Public transport has lost its competitive edge to private cars because people tend to prefer more convenient modes as their income increases. A promising way to reverse this trend is to provide more convenient modes of transport in terms of travel times and amenity. In Korea, we have implemented several policy measures aimed at increasing the attractiveness of public transport by reducing travel times and by providing more seats, etc. This paper analyses the post-policy impacts of these measures and compares the results with those of an ex ante quantitative policy effectiveness analysis. The main policy implication from the empirical analysis is that increasing the convenience level of public transport can be an effective way to increase public transport patronage. The measures to achieve this include reducing public transport travel times by increasing speeds or reducing headways, and by enhancing amenity levels. Following the reform of Seoul's public transport system, which reduced travel times by introducing exclusive median bus lanes and integrated public transport fares, we have actually seen an increase in the number of public transport users.
Keywords: 330